Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.3596
|View full text |Cite
|
Sign up to set email alerts
|

AB1455-HPR The experience of living with fatigue among people with rheumatoid arthritis – a qualitative meta-synthesis

Abstract: BackgroundPeople with Rheumatoid Arthritis (RA) experience fatigue as the most significant symptom of their illness. Despite a substantial body of knowledge about fatigue, there is a need for an overall comprehensive understanding of the experience of living with fatigue among people with RAObjectivesTo identify, appraise and synthesise qualitative studies on experiences of living with fatigue in people with RAMethodsWe conducted a qualitative meta-synthesis, inspired by Sandelowski and Barroso1. This included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Pain can lead to poor sleep, depressed mood and fatigue, all of which are connected. 6 18 28 31 32 Also, more than 10% of patients with RA have fibromyalgia 33 and 10% report depression in ERA. 26 Behavioural and psychological factors are more likely explanations of fatigue in RA and not disease activity.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Pain can lead to poor sleep, depressed mood and fatigue, all of which are connected. 6 18 28 31 32 Also, more than 10% of patients with RA have fibromyalgia 33 and 10% report depression in ERA. 26 Behavioural and psychological factors are more likely explanations of fatigue in RA and not disease activity.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Like other authors, we did not find a significant effect of inflammation on the development of fatigue in RA patients. Similarly, also Van Hoogmoed et al (2010), andRepping-Wuts et al (2007) reported that pain, disability, depression, and low self-efficacy were associated with greater fatigue, but inflammatory indices were not correlated with fatigue severity. The fatigue in RA patients may be only partially related to disease activity, which may have accounted for poor agreement with respect to a fatigue domain within a flare questionnaire in RA (Pope, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Fatigue is often present even if RA activity is low. This can be due to common chronic pain in RA, which can lead to poor sleep, depressed mood, and fatigue (Katz, 2017;Bingham et al, 2019;Junghaenel et al, 2019;Primdahl et al, 2019;Silva et al, 2019). Also, 10% of RA patients report depression in early RA (Holdren et al, 2019).…”
Section: Introductionmentioning
confidence: 99%